Turning logical expression around

Posted by BluePrint on Stack Overflow See other posts from Stack Overflow or by BluePrint
Published on 2013-11-10T08:46:30Z Indexed on 2013/11/10 9:53 UTC
Read the original article Hit count: 125

Filed under:
|
|

I have the following code:

bool s = true;

for (...; ...; ...) {
    // code that defines A, B, C, D 
    // and w, x, y, z

    if (!(A < w) && s == true) {
        s = false;
    }

    if (!(B < x) && s == true) {
        s = false;
    }

    if (!(C < y) && s == true) {
        s = false;
    }

    if (!(D < z) && s == true) {
        s = false;
    }
}

This code is working well. However, I want to, for several (unimportant) reasons, change the code so that I can initiate s = false; and set it to true inside the if-statement. It tried the following:

bool s = false;

for (...; ...; ...) {
    // code that defines A, B, C, D 
    // and w, x, y, z

    if (A >= w && s == false) {
        s = true;
    }

    if (B >= x && s == false) {
        s = true;
    }

    if (C >= y && s == false) {
        s = true;
    }

    if (D >= z && s == false) {
        s = true;
    }
}

However, this is not working properly as the code above is working. I know thought wrong somewhere in the logic, but I can't figure out where. Does anbyone see my probably obvious error?

EDIT: Added three more if-statemets. Missed them since they were commented away.

© Stack Overflow or respective owner

Related posts about c++

Related posts about if-statement